Issues concerning the dynamics of labor productivity at the level of the companies in Constanta County operating in the Construction sector before and after the COVID-19 pandemic - Stan, Mari-Isabella (Technium Social Sciences Journal, 2021)
The construction industry sector plays an important role in the national and local economy, and its activities are vital for achieving the objectives of economic and social development which lead to increasing the citizens' quality of life. In the construction sector, the COVID-19 crisis has led to a reduction in site productivity, which has led to an increase in compliance costs, delayed projects and increased the exposure of construction workers to risk and infection. Given that many companies have experienced substantial declines in turnover and high turnover uncertainty during this pandemic, a continuous analysis of the economic climate, respectively of the main indicators of the companies active on the market is a very important element in terms of outlining an overall view of the current situation, as well as the trends in the construction sector. This study provides an empirical analysis as to before and after the COVID-19 pandemic level of labor productivity of economic agents operating in the construction sector in Constanta County. Starting from assessments of the average turnover and the evolution of the workforce of the companies in the construction sector located on the territory of Constanta County, the objective of the research was the dynamical analysis of the level of labor productivity and the way it was influenced by the emergence of this unexpected event. The obtained results confirmed the research hypothesis, namely that the level of labor productivity is influenced by the level of investment and it registers a moderate increase, yet on a noticeable increasing trend, the probable reason being the construction projects for public investment carried out in the area.